2014
DOI: 10.1111/ajr.12117
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the effect of infrastructure on fly‐in fly‐out mining workers

Abstract: Recreational infrastructure and activities enhance the experience of FIFO workers at mining camps. The availability of quality recreational facilities helps promote social interaction, provides for greater social inclusion and improves the experience of mining camps for their temporary FIFO residents. The infrastructure also needs to allow for privacy and individual recreational activities, which participants identified as important emotional needs. Developing appropriate recreational infrastructure at mining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Nonetheless, FIFO workers may benefit from having access to on-site recreational facilities (eg, gymnasiums, sports courts). Previous research showed that FIFO mining workers with access to such facilities enjoyed the opportunities to exercise and felt a stronger sense of community 8. Using such facilities may also promote displacement of prevalent unhealthy on-site behaviours, such as excessive alcohol consumption 9…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, FIFO workers may benefit from having access to on-site recreational facilities (eg, gymnasiums, sports courts). Previous research showed that FIFO mining workers with access to such facilities enjoyed the opportunities to exercise and felt a stronger sense of community 8. Using such facilities may also promote displacement of prevalent unhealthy on-site behaviours, such as excessive alcohol consumption 9…”
Section: Discussionmentioning
confidence: 99%
“…For example, shift type (night vs day) and roster length may be important factors in determining the level of daily job demands and stressors, which in turn may influence engagement in health behaviour, and health outcomes (but see Paech et al 16). Availability of health-supportive infrastructure is also likely to influence health and was not assessed in our study: access to recreational facilities including gymnasiums, sports courts and healthy food options facilitate health behaviours, whereas accessible pubs and unhealthy food options permit unhealthy behaviours while on-site 8. Additionally, our study contained only a small subgroup of data for both partners in a relationship, so dyadic modelling and actor–partner effects were not able to be tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 Another study did not recruit a general population comparison group, only comparing the prevalence of drinking among offshore rotation workers with secondary data source among general male population, and reported higher prevalence of heavy drinkers among offshore rotation workers (approximately 30% vs 10% heavy drinkers). 55 Similarly, two qualitative studies 84 110 described onshore work camps as having a strong 'culture of drinking', 110 and another qualitative study 49 noted some offshore workers indicated that the high levels of alcohol consumption among offshore workers should change.…”
Section: Social Supportmentioning
confidence: 99%
“…The social makeup of RBCs contributes to many of the documented concerns and the instability typical in these communities and is largely associated with a primarily male workforce who are away from their partners and families (Gill 1991;Hostetter 2011;Connell 2016). The social structures in RBCs are influenced by industry employment practices and case studies into RBCs in Australia and Canada have highlighted the relationship between employment structures and community well-being (Storey 2001;Carrington and Pereira 2011;Hoath and Haslam-McKenzie 2013;McKenzie et al 2014;Perring et al 2014;Marais et al 2018).…”
Section: Workforce Structuresmentioning
confidence: 99%